2023
DOI: 10.3389/fcdhc.2023.1177030
|View full text |Cite
|
Sign up to set email alerts
|

The impact of structured self-monitoring of blood glucose on clinical, behavioral, and psychosocial outcomes among adults with non-insulin-treated type 2 diabetes: a systematic review and meta-analysis

Abstract: BackgroundSelf-monitoring of blood glucose (SMBG) is considered of little clinical benefit for adults with non-insulin-treated type 2 diabetes, but no comprehensive review of a structured approach to SMBG has been published to date.PurposeTo conduct a systematic review and meta-analysis of the impact of sSMBG on HbA1c, treatment modifications, behavioral and psychosocial outcomes, and; examine the moderating effects of sSMBG protocol characteristics on HbA1c.Data sourcesFour databases searched (November 2020; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…The objective of this shed novel light on the under-researched topic of the characteristics fostering the usability of such devices in order to increase adherence to the therapy. Indeed, prior studies have demonstrated a positive impact of structured SMBG on confidence in self-managing diabetes, which in turn leads to improvement in HbA1c (glycated haemoglobin) ( 24 ). Additionally, some evidence has shown that structured SMBG can provide psychosocial benefits to patients, fostering ongoing relevant debates about the most appropriate tools and methods ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…The objective of this shed novel light on the under-researched topic of the characteristics fostering the usability of such devices in order to increase adherence to the therapy. Indeed, prior studies have demonstrated a positive impact of structured SMBG on confidence in self-managing diabetes, which in turn leads to improvement in HbA1c (glycated haemoglobin) ( 24 ). Additionally, some evidence has shown that structured SMBG can provide psychosocial benefits to patients, fostering ongoing relevant debates about the most appropriate tools and methods ( 25 ).…”
Section: Discussionmentioning
confidence: 99%